Pengaruh implementasi teori konseling behavior dengan teknik self-management untuk mengatasi perilaku membolos pada siswa di sekolah menengah pertama swasta - Br Tambunan, Rugun Gabriella; Tambunan, Rugun Gabriella Br (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This study aims to determine the effectiveness of behavioral counseling services with self-management tactics of SMP Santo Yoseph Medan. The location of the research was at SMP Santo Yoseph Medan. Class VII with a total of 6 student at SMP Santo Yoseph Medan. The method used in this research is Experiment. Sampling using purposive sampling technique. Data collection uses a truant behavior questionnaire. The data analysis technique uses statistical parametric analysis, namely by using the paired-sample T-Test with the help of the SPSS for windows vers 16.00 program. This research method aims to determine the effect of individual counseling through a behavioral approach with self management techniques in overcoming truant student behavior. In this study focusing on the effectiveness of behavioral counseling services with the Self Management techniques in overcome truant behavior of students with the data collection technique used, namely questionnaires. In this study the experimental design was used because there are still dependent variables, the experimental results which are the dependent variable are solely influenced by the independent variable, this occurs because there is no control variable, and the sample is not randomly selected.